Assessing soil quality under different land cover types within shifting agriculture in South Cameroon - Ngo-Mbogba, M.; Yemefack, Martin; Nyeck, B. (Elsevier, 2015)
The common agricultural practice in the humid tropical forest zone of Cameroon is shifting cultivation, which leads to a landscape mosaic system characterized by a diversity of land cover types. Our objective was to evaluate soil properties and soil quality under these land cover types and to investigate on their interrelationships. Topsoil samples (0–20 cm) were collected at the same time from 8 different land cover types (bare soil with burned vegetation biomass (FR1), bare soil with unburned vegetation biomass (FR), Chromolaena odorata fallow (JC), bush ligneous fallow (JR), secondary forest (SF), primary forest (FC), Gilbertiodendron dewevrei forest (FG), and raffia and Uapacca forest (RA)) and analysed for routine laboratory determinations. A soil quality index (SQI) computed based on soil chemical properties, analysis of variance and multiple comparison tests were used to compare soils from different land cover types. Principal component analysis (PCA) was used to select the most appropriate indicators that control soil quality. Several soil properties showed high to very high coefficient of variation within the land cover types. Organic matter was significantly high under forested land cover types (FC, FG, RA) and under bare soil with burned vegetation (FR1). Soil quality differs significantly (p = 0.000) from one land cover to another and shows the following ranking: SQI_FR1